1998
DOI: 10.1086/311737
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Evolution of Universal Dark Matter Halo Density Profiles

Abstract: Dark matter halos show a universal density profile with a scaling such that less massive systems are typically denser. This mass-density relation is well described by a proportionality between the characteristic density of halos and the mean cosmic density at halo formation time. It has recently been shown that this proportionality could be the result of the following simple evolutionary picture. Halos form in major mergers with essentially the same, cosmogony-dependent, dimensionless profile and then grow ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…SSM found that, given an effective value of Δ m of about , the empirical mass–density relation shown by haloes in high‐resolution N ‐body simulations of distinct hierarchical cosmologies (Navarro, Frenk & White 1997, hereafter NFW) is naturally reproduced under the assumption proposed by NFW that the characteristic density of haloes is proportional to the critical density of the universe at the time of their formation. Raig, González‐Casado & Salvador‐Solé (1998, hereafter RGS) subsequently showed that the mass–density relation is, in this case, not only consistent with but actually implied by the MPS model. To prove this, RGS assumed haloes endowed with a universal density profile à la NFW.…”
Section: Introductionsupporting
confidence: 66%
“…SSM found that, given an effective value of Δ m of about , the empirical mass–density relation shown by haloes in high‐resolution N ‐body simulations of distinct hierarchical cosmologies (Navarro, Frenk & White 1997, hereafter NFW) is naturally reproduced under the assumption proposed by NFW that the characteristic density of haloes is proportional to the critical density of the universe at the time of their formation. Raig, González‐Casado & Salvador‐Solé (1998, hereafter RGS) subsequently showed that the mass–density relation is, in this case, not only consistent with but actually implied by the MPS model. To prove this, RGS assumed haloes endowed with a universal density profile à la NFW.…”
Section: Introductionsupporting
confidence: 66%
“…where ρ c and r s are, respectively, the halo characteristic density and scale radius. Salvador-Solé, Solanes, & Manrique (1998; see also Raig, González-Casado, & Salvador-Solé 1998) developed a consistent analytic description of the hierarchical evolution of DM halos that provides an excellent fit to Nbody simulations (Raig, González-Casado, & Salvador-Solé 2001). This framework for structure formation incorporates in the well-known extended Press-Schechter formalism (Lacey & Cole 1993) a pre-established phenomenological threshold ∆ m setting the fractional mass increase that separates the two basic mass aggregation regimes of dark halos: minor mergers or accretion, where these objects grow inside-out through the continuous aggregation of small clumps that do not disturb their internal structure 3 , and major merger events, in which the progenitor halos are fully disrupted giving rise to the formation of a new bound system.…”
Section: The Dark Halo Evolution Modelmentioning
confidence: 99%
“… These are actually formulae for fast mass gain and can include accretion. Analytic formulae differentiating between major mergers and accretion have been found by Raig, Gonzalez‐Casado & Salvador‐Sole (1998), Salvador‐Sole, Solanes & Manrique (1998) and Andreu, Gonzalez‐Casado & Salvador‐Sole (2001). …”
mentioning
confidence: 92%
“…These are actually formulae for fast mass gain and can include accretion. Analytic formulae differentiating between major mergers and accretion have been found byRaig, Gonzalez-Casado & Salvador-Sole (1998), Salvador-Sole, Solanes & Manrique (1998) andAndreu, Gonzalez-Casado & Salvador-Sole (2001).4 If the m 0 halo has come from an m i halo, all of its mass was not previously in the m i halo, only m i /m 0 of its mass. But the quantity wanted here is the full mass of haloes which have had mergers, i.e.…”
mentioning
confidence: 93%